PERAN KEPALA SEKOLAH DALAM MENINGKATKAN KEDISIPLINAN TERHADAP SISWA SMP N I SIBERUT SELATAN KEBUPATEN KEPULAUAN MENTAWAI - Kristina, Lina - (Pendidikan Sosiologi, 2014)
This research was about the role of headmasters to improve the studentsâ discipline at SMP N 1 Siberut Selatan. The aim of this research was to: 1) reveal the factors triggering the students to break the rules applied at SMP N 1 Siberut Selatan, 2) figure out the role of headmaster to overcome the problem and improve the studentsâ discipline at SMP N 1 Siberut Selatan. To conduct this research, the structural functional theory developed by George Ritzer was applied. This was a descriptive research which used qualitative approach. The informants of the research were a headmaster, three teachers and seven students breaking the rules. The data was collected through observation, interview and documentation. The data gathered was analyzed descriptively by involving several steps including collecting the data, reducing the data, presenting the data and drawing conclusion. The result of the research showed that the factors triggering the students to break the rules were: 1) the studentsâ houses were far from school, 2) the lack of means of transportation, and 3) the studentsâ lack of awareness of the rules. In order to improve the studentsâ discipline, the headmaster: 1) motivated the teachers or the class teachers, 2) socialized the school rules to the students, and 3) gave punishment to the students breaking the rules. Based on these results, it was concluded that the factors triggering the students to break the rules were the distance between their house and school, transportation and their awareness. Meanwhile, the roles of the headmaster to improve the studentsâ discipline were motivating the teachers, socializing the rules to the students, and giving punishment to those breaking the rules.